Pokemon Go Sebagai Saluran Komunikasi Pemasaran Alternatif - Inco Hary Perdana (Ultimacomm: Jurnal Ilmu Komunikasi, 2017)
Pokemon Go is a new phenomenon in the game industry. Within a month from its launching, this game had been played by more than 75 million users. The game has been seen as an opportunity in marketing communication by several brands. This study seeks to find the use of the game in marketing communication activities by analyzing it with the concept of marketing mix by Belch and Belch (2012) and Horwitz’s classification in game advertisement (2004) in Skalski, Bracken, and Buncher (2011). The literature review explores several documents and promotional materials which used Pokemon Go and analyzed them based on the concepts above. The study shows that many brands only used the popularity of Pokomen Go but did not officially establish affiliation with Pokemon Go. When Pokemon Go was launched, McDonald was the first to become the official partner of the game. The analysis also finds the expansive collaboration opportunities of the brand in digital marketing communication and in-game advertisement as long as they can combine the ideas, creativity, and the technology. Keywords: Pokemon Go, digital marketing mix, in game advertisement.